Non-Carcinogenic Health Risk of Trace Metals in Artesian Well Waters - Inghug, Delicia C. (Health Notions, 2018)
Levels of lead, copper, zinc, nickel and cadium were assessed in artesian well waters of Agua dulce, Linao, Cogon and Punta in Ormoc City, Leyte, Philippines. Samples of water in three replicates each from the four study sites were brought to the Visayas State University Analytical laboratory to determine the presence of dissolved trace metals using atomic absorption spectrophotometer. Non-carcinogenic health risk of the trace metals for children and adults was also determined using the chronic daily intake of trace metals and hazard quotient index. Results revealed that lead and cadmium were found to be beyond the WHO permissible limits in all areas studied. Hazard quotient greater than 1 in all study sites was found in lead for both children and adults and in cadmium in children. Total hazard quotient of trace metals in the four study sites was found higher than 1 in both children and adults. These results indicate a non-carcinogenic health risk to the people which call for immediate attention and concern by the local authorities. Keywords: Non-carcinogenic risk, Health risk assessment, Trace metals, Artesian well waters